Aflatoxin B1 impairs porcine oocyte quality via disturbing intracellular membrane system and ATP production - Lin-Lin Hu; Shun Chen; Meng-Ying Shen; Qiu-Yan Huang; Hong-Ge Li; Shao-Chen Sun; Jun-Li Wang; Xiao-Qiong Luo (Ecotoxicology and Environmental Safety, 2023)
Aflatoxin is the most common type of mycotoxins in contaminated corn, peanuts and rice, which affects the livestock and ultimately endangers human health. Aflatoxin is reported to have carcinogenicity, mutation, growth retardation, immunosuppression and reproductive toxicity. In present study we reported the causes for the declined porcine oocyte quality under aflatoxin exposure. We set up an in vitro exposure model and showed that aflatoxin B1 disturbed cumulus cell expansion and oocyte polar body extrusion. We found that aflatoxin B1 exposure disrupted ER distribution and elevated the expression of GRP78, indicating the occurrence of ER stress, and the increased calcium storage also confirmed this. Besides, the structure of cis-Golgi apparatus, another intracellular membrane system was also affected, showing with decreased GM130 expression. The oocytes under aflatoxin B1 exposure showed aberrant lysosome accumulation and higher LAMP2 expression, a marker for lysosome membrane protection, and this might be due to the aberrant mitochondria function with low ATP production and the increase of apoptosis, since we found that BAX expression increased, and ribosomal protein which is also an apoptosis-related factor RPS3 decreased. Taken together, our study revealed that aflatoxin B1 impairs intracellular membrane system ER, Golgi apparatus, lysosome and mitochondria function to affect porcine oocyte maturation quality.